2002
DOI: 10.1063/1.1496129
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes as a tip calibration standard for electrostatic scanning probe microscopies

Abstract: Scanning Surface Potential Microscopy (SSPM) is one of the most widely used techniques for the characterization of electrical properties at small dimensions.Applicability of SSPM and related electrostatic scanning probe microscopies for imaging of potential distributions in active micro-and nanoelectronic devices requires quantitative knowledge of tip-surface contrast transfer. Here we demonstrate the utility of carbonnanotube-based circuits to characterize geometric properties of the tip in the electrostatic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…The EFM signal from a nanotube on an insulator is known to be well described, empirically, by a Lorentzian function of the distance x perpendicular to the nanotube. 16,17 We find that tmSGM peaks such as that in Figure 3 are also accurately fit by Lorentzians, consistent with the parallel between tmSGM and EFM. The narrower linewidth for tmSGM compared with SGM can then be quantified as follows.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The EFM signal from a nanotube on an insulator is known to be well described, empirically, by a Lorentzian function of the distance x perpendicular to the nanotube. 16,17 We find that tmSGM peaks such as that in Figure 3 are also accurately fit by Lorentzians, consistent with the parallel between tmSGM and EFM. The narrower linewidth for tmSGM compared with SGM can then be quantified as follows.…”
supporting
confidence: 76%
“…16 (~ μm) decay back to steady state, which is not evident in the tmSGM signal. The better signal to noise ratio is a result of the lock-in detection scheme, as has been employed for SGM before.…”
mentioning
confidence: 90%
“…SWNT devices are an excellent test case that have proven to be quite complex in past research. 12,13,[16][17][18][19][20][21][22][23] Because of their extremely small diameters (1 nm) and low carrier densities (1 to 100 lm À1 ), SWNT channels couple very weakly to KPFM probe tips 12 and some researchers have concluded that SWNT potential gradients are too small to image reliably. 13,16,22 Devices in our study consisted of dilute SWNTs synthesized by chemical vapor deposition directly on 4 00 p þþ silicon wafers with 250 nm backgate oxides.…”
Section: -mentioning
confidence: 99%
“…The crucial issue to understand KFM experiments on transistors is to derive quantitative information from KFM images, even though the role of side capacitances has been pointed out earlier [15,43]. We here present a KFM study performed on Pd-contacted CNTFETs fabricated on an ∼ 320 nm-thick SiO 2 layer, which addresses this issue [48].…”
Section: Kfm Determination Of the Lever Arm Of A Cntfetmentioning
confidence: 91%